Carbon material doped with nitrogen and phosphorus heteroatoms, method for its preparation and use in rubber

CN122771364BActive Publication Date: 2026-10-27HEBEI BAOLI ENG EQUIP GRP CO LTD +3
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611265379.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-27
Estimated Expiration
2046-08-20

AI Technical Summary

Benefits of technology

[0029]本发明以壳聚糖盐酸盐、壳二糖盐酸盐或壳四糖四盐酸盐作为碳源,与聚乙烯吡咯烷酮复配,并加入氮源、磷源、KCl和/或NaCl,得到了一种掺杂氮磷杂原子的碳材料,经实验验证,该碳材料具有较大的比表面积与孔容以及作为橡胶止水带补强剂的效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122771364B_ABST
    Figure CN122771364B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of carbon materials, and particularly relates to a carbon material doped with nitrogen and phosphorus heteroatoms, a preparation method thereof and application of the carbon material in rubber, wherein the carbon material is prepared by the following method: S1: dissolving a carbon source and polyvinylpyrrolidone in water to obtain a mixture A by stirring; mixing and grinding melamine phosphate and a nitrogen source to obtain a solid mixture B; S2: under the condition of heating and stirring, adding the solid mixture B into the mixture A in batches to obtain a gel; adding potassium chloride and / or sodium chloride into the gel, and continuously heating and stirring to obtain an intermediate product C; S3: freeze-drying the intermediate product C, and then calcining the freeze-dried intermediate product C in a tube furnace in a protective atmosphere to obtain a black solid, and obtaining the carbon material through post-treatment; the carbon material obtained by the application can produce good actual effects in the field of rubber waterstop, and has important market value and practical significance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of carbon materials technology, specifically relating to a carbon material doped with nitrogen and phosphorus heteroatoms, its preparation method, and its application in rubber. Background Technology

[0002] Carbon materials, with carbon as their primary constituent element, possess a wide variety of properties due to the diverse hybridization of carbon's electronic orbitals. These properties include a large specific surface area, strong adsorption capacity, and abundant surface functional groups. Furthermore, carbon materials are inexpensive and widely available, making them suitable as catalysts, catalyst supports, adsorbents, and electrodes, and leading to their extensive applications in catalysis, adsorption, and electrochemistry. Despite the inherent good performance of carbon materials, further improvements are needed in certain specific reactions or applications. Heteroatom doping (N, B, S, P, etc.) can further enhance the physicochemical properties of carbon materials, thereby optimizing their applications in these fields.

[0003] Regarding the development of nitrogen-containing carbon materials, the inventors have previously conducted a series of studies, such as CN201911004675.2, which involves a method for preparing nitrogen-containing carbon materials based on polyaspartic acid salt and its application. The polyaspartic acid salt is placed in a carbonization furnace and carbonized under vacuum conditions to obtain a black nitrogen-containing carbon material. After acid washing, the nitrogen-containing carbon material is obtained. The nitrogen-containing carbon material obtained by the provided method has a large specific surface area and a more uniform distribution of nitrogen atoms and pore size.

[0004] With the increasing market demand for carbon materials, it is of great significance to develop a carbon material doped with nitrogen and phosphorus heteroatoms for use in rubber reinforcing agents. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a carbon material doped with nitrogen and phosphorus heteroatoms, a method for its preparation, and its application in rubber.

[0006] To solve the above problems, the technical solution adopted by the present invention is as follows:

[0007] Technical Topic 1

[0008] A carbon material doped with nitrogen and phosphorus heteroatoms is prepared as follows:

[0009] S1: Dissolve the carbon source and polyvinylpyrrolidone in water and stir to obtain mixture A; mix and grind melamine phosphate and nitrogen source to obtain solid mixture B;

[0010] S2: Under heating and stirring, solid mixture B is added to mixture A in portions to obtain a gel; under continuous heating and stirring, chloride salt is added to the gel and stirred evenly to obtain intermediate product C;

[0011] S3: After freeze-drying the intermediate product C, it is placed in a tube furnace and calcined in a protective atmosphere to obtain a black solid, which is then post-processed to obtain carbon materials.

[0012] The carbon source includes one or more of chitosan hydrochloride, chitobiose hydrochloride, and chitotetraose tetrahydrochloride;

[0013] The nitrogen source includes one or more of cyanuric acid, thiocyanuric acid, cyanuric acid diamide, and hexachlorotriphosphazene.

[0014] The chloride salt is sodium chloride and / or potassium chloride.

[0015] As a further improvement of the present invention, the addition in step S2 is divided into 5 to 10 portions, with one portion added every 5 to 10 minutes.

[0016] As a further improvement of the present invention, the mass ratio of the carbon source, melamine phosphate, nitrogen source, polyvinylpyrrolidone, and chloride salt is 10:2~4:2~4:3~5:3~5.

[0017] As a further improvement of the present invention, the mass ratio of the carbon source, melamine phosphate, nitrogen source, polyvinylpyrrolidone, and chloride salt is 10:3:3:4:4.

[0018] As a further improvement of the present invention, the ratio of carbon source to water in S1 is 1g: 3~20ml.

[0019] As a further improvement of the present invention, the stirring temperature in S1 is 50~90℃ and the stirring time is 30~50min;

[0020] The heating and stirring temperature in S2 is 50~90℃.

[0021] As a further improvement of the present invention, the freeze-drying temperature is -80~-100℃; the freeze-drying time is 15~25h.

[0022] As a further improvement of the present invention, the calcination is as follows: the temperature is increased from room temperature to 180-300°C at a rate of 2-4°C / min and held for 0.5-1.5h; the temperature is increased to 1450-1650°C at a rate of 4-6°C / min and held for 1-3h; and finally the temperature is reduced to room temperature at a rate of 3-5°C / min.

[0023] As a further improvement of the present invention, the post-treatment is washing with 0.1~2M hydrochloric acid and then rinsing with water until no chlorine residue remains.

[0024] Technical Theme Two

[0025] A method for preparing a carbon material doped with nitrogen and phosphorus heteroatoms as described in Technical Subject 1.

[0026] Technical Theme 3

[0027] Application of a carbon material doped with nitrogen and phosphorus heteroatoms as described in Technical Subject 1 in the field of rubber waterstops.

[0028] The beneficial effects of adopting the above technical solution are as follows:

[0029] This invention uses chitosan hydrochloride, chitobiose hydrochloride, or chitosan tetrahydrochloride as a carbon source, compounded with polyvinylpyrrolidone, and adds nitrogen source, phosphorus source, KCl and / or NaCl to obtain a carbon material doped with nitrogen and phosphorus heteroatoms. Experimental verification shows that this carbon material has a large specific surface area and pore volume, as well as the effect of being a reinforcing agent for rubber waterstops. Attached Figure Description

[0030] Figure 1 This is a SEM image of the carbon material doped with nitrogen and phosphorus heteroatoms obtained in Example 1 of this invention;

[0031] Figure 2 This is the nitrogen adsorption-desorption curve of the carbon material doped with nitrogen and phosphorus heteroatoms obtained in Example 1 of this invention;

[0032] Figure 3 This is a particle size distribution diagram of the carbon material doped with nitrogen and phosphorus heteroatoms obtained in Example 1 of the present invention. Detailed Implementation

[0033] To make the objectives, technical solutions, and advantages of the present invention clearer, the invention will be described clearly and completely below in conjunction with specific embodiments.

[0034] The chitosan hydrochloride used in this application was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., item number B304452;

[0035] Polyvinylpyrrolidone was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., item number P1511429.

[0036] Example 1

[0037] S1: 10 g of chitosan hydrochloride and 4 g of polyvinylpyrrolidone were dissolved in 50 mL of deionized water and stirred at 70 °C for 40 minutes to obtain mixture A; 3 g of melamine phosphate and 3 g of cyanuric acid were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0038] S2: Divide the solid mixture B into 10 equal parts, and add one part to solution A every 5 minutes. Continue stirring at 70°C to obtain a white gel. Take a mixture of 2 g potassium chloride and 2 g sodium chloride, grind them and pass them through a 100-mesh sieve, and add it to the white gel all at once. Keep stirring at 70°C for 15 minutes to obtain product C.

[0039] S3: After freeze-drying product C at -90℃ for 20 hours, it was placed in a tubular carbonization furnace, nitrogen gas was introduced, and the temperature was increased from room temperature to 240℃ at a rate of 3℃ / min. After holding at 240℃ for 1 hour, the temperature was increased to 1550℃ at a rate of 5℃ / min and held at 1550℃ for 2 hours. Finally, the temperature was decreased to room temperature at a rate of 4℃ / min to obtain a black solid product. The black solid product was washed with 1M hydrochloric acid aqueous solution and then washed with water until neutral to obtain the carbon material. The content of N and P in the product was analyzed by X-ray photoelectron spectroscopy. The results showed that the N content was 6.83% and the phosphorus content was 1.37%.

[0040] Example 2

[0041] S1: 10 g of chitobiose hydrochloride and 4 g of polyvinylpyrrolidone were dissolved in 50 mL of deionized water and stirred at 50 °C for 50 minutes to obtain mixture A; 3 g of melamine phosphate and 3 g of cyanuric acid were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0042] S2: Divide the solid mixture B into 10 equal parts, and add one part to solution A every 5 minutes. Continue stirring at 70°C to obtain a white gel. Take a mixture of 2 g potassium chloride and 2 g sodium chloride, grind them and pass them through a 100-mesh sieve, and add it to the white gel all at once. Keep stirring at 70°C for 15 minutes to obtain product C.

[0043] S3: After freeze-drying product C at -80℃ for 25 hours, place it in a tubular carbonization furnace, introduce nitrogen gas, heat from room temperature to 240℃ at a heating rate of 3℃ / min, hold at 240℃ for 1 hour, then heat to 1550℃ at a rate of 5℃ / min, hold at 1550℃ for 2 hours, and finally cool to room temperature at a rate of 4℃ / min to obtain a black solid product; wash the black solid product with 1M hydrochloric acid aqueous solution and then wash with water until neutral to obtain the product carbon material.

[0044] Example 3

[0045] S1: 10 g of chitosan tetrahydrochloride and 4 g of polyvinylpyrrolidone were dissolved in 50 mL of deionized water and stirred at 90 °C for 30 minutes to obtain mixture A; 3 g of melamine phosphate and 3 g of cyanuric acid were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0046] S2: Divide the solid mixture B into 10 equal parts, and add one part to solution A every 5 minutes. Continue stirring at 70°C to obtain a white gel. Take a mixture of 2 g potassium chloride and 2 g sodium chloride, grind them and pass them through a 100-mesh sieve, and add it to the white gel all at once. Keep stirring at 70°C for 15 minutes to obtain product C.

[0047] S3: After freeze-drying product C at -100℃ for 15 hours, place it in a tubular carbonization furnace, introduce nitrogen gas, heat from room temperature to 240℃ at a heating rate of 3℃ / min, hold at 240℃ for 1 hour, then heat to 1550℃ at a rate of 5℃ / min, hold at 1550℃ for 2 hours, and finally cool to room temperature at a rate of 4℃ / min to obtain a black solid product; wash the black solid product with 1M hydrochloric acid aqueous solution and then wash with water until neutral to obtain the carbon material.

[0048] Example 4

[0049] S1: 10 g of chitosan hydrochloride and 4 g of polyvinylpyrrolidone were dissolved in 50 mL of deionized water and stirred at 70 °C for 40 minutes to obtain mixture A; 3 g of melamine phosphate and 3 g of thiocyanate were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0050] S2: Divide the solid mixture B into 10 equal parts, and add one part to solution A every 5 minutes. Continue stirring at 70°C to obtain a white gel. Take a mixture of 2 g potassium chloride and 2 g sodium chloride, grind them and pass them through a 100-mesh sieve, and add it to the white gel all at once. Keep stirring at 70°C for 15 minutes to obtain product C.

[0051] S3: After freeze-drying product C at -90℃ for 20 hours, place it in a tubular carbonization furnace, introduce nitrogen gas, heat from room temperature to 180℃ at a heating rate of 2℃ / min, hold at 180℃ for 1.5 hours, then heat to 1650℃ at a rate of 6℃ / min, hold at 1650℃ for 1 hour, and finally cool to room temperature at a rate of 3℃ / min to obtain a black solid product; wash the black solid product with 1M hydrochloric acid aqueous solution and then wash with water until neutral to obtain the product carbon material.

[0052] Example 5

[0053] S1: 10 g of chitosan hydrochloride and 4 g of polyvinylpyrrolidone were dissolved in 50 mL of deionized water and stirred at 70 °C for 40 minutes to obtain mixture A; 3 g of melamine phosphate and 3 g of cyanuric acid diamide were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0054] S2: Divide the solid mixture B into 10 equal parts, and add one part to solution A every 5 minutes. Continue stirring at 70°C to obtain a white gel. Take a mixture of 2 g potassium chloride and 2 g sodium chloride, grind them and pass them through a 100-mesh sieve, and add it to the white gel all at once. Keep stirring at 70°C for 15 minutes to obtain product C.

[0055] S3: After freeze-drying product C at -90℃ for 20 hours, place it in a tubular carbonization furnace, introduce nitrogen gas, heat from room temperature to 300℃ at a heating rate of 4℃ / min, hold at 300℃ for 0.5h, then heat to 1450℃ at a rate of 4℃ / min, hold at 1450℃ for 3h, and finally cool to room temperature at a rate of 5℃ / min to obtain a black solid product; wash the black solid product with 1M hydrochloric acid aqueous solution and then wash with water until neutral to obtain the carbon material.

[0056] Example 6

[0057] S1: 10 g of chitosan hydrochloride and 4 g of polyvinylpyrrolidone were dissolved in 50 mL of deionized water and stirred at 70 °C for 40 minutes to obtain mixture A; 3 g of melamine phosphate and 3 g of hexachlorotriphosphazene were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0058] S2: Divide the solid mixture B into 10 equal parts, and add one part to solution A every 5 minutes. Continue stirring at 70°C to obtain a white gel. Take a mixture of 2 g potassium chloride and 2 g sodium chloride, grind them and pass them through a 100-mesh sieve, and add it to the white gel all at once. Keep stirring at 70°C for 15 minutes to obtain product C.

[0059] S3: After freeze-drying product C at -90℃ for 20 hours, place it in a tubular carbonization furnace, introduce nitrogen gas, heat from room temperature to 240℃ at a heating rate of 3℃ / min, hold at 240℃ for 1 hour, then heat to 1550℃ at a rate of 5℃ / min, hold at 1550℃ for 2 hours, and finally cool to room temperature at a rate of 4℃ / min to obtain a black solid product; wash the black solid product with 1M hydrochloric acid aqueous solution and then wash with water until neutral to obtain the product carbon material.

[0060] Example 7

[0061] S1: 10 g of chitosan hydrochloride and 3 g of polyvinylpyrrolidone were dissolved in 50 mL of deionized water and stirred at 70 °C for 40 minutes to obtain mixture A; 2 g of melamine phosphate and 2 g of cyanuric acid were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0062] S2: Divide the solid mixture B into 10 equal parts, and add one part to solution A every 5 minutes. Continue stirring at 70°C to obtain a white gel. Take a mixture of 2.5 g potassium chloride and 2.5 g sodium chloride, grind them and pass them through a 100-mesh sieve, and add it to the white gel all at once. Keep stirring at 70°C for 15 minutes to obtain product C.

[0063] S3: After freeze-drying product C at -90℃ for 20 hours, place it in a tubular carbonization furnace, introduce nitrogen gas, heat from room temperature to 240℃ at a heating rate of 3℃ / min, hold at 240℃ for 1 hour, then heat to 1550℃ at a rate of 5℃ / min, hold at 1550℃ for 2 hours, and finally cool to room temperature at a rate of 4℃ / min to obtain a black solid product; wash the black solid product with 1M hydrochloric acid aqueous solution and then wash with water until neutral to obtain the product carbon material.

[0064] Example 8

[0065] S1: 10 g of chitosan hydrochloride and 5 g of polyvinylpyrrolidone were dissolved in 50 mL of deionized water and stirred at 70 °C for 40 minutes to obtain mixture A; 4 g of melamine phosphate and 4 g of cyanuric acid were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0066] S2: Divide the solid mixture B into 10 equal parts, and add one part to solution A every 5 minutes. Continue stirring at 70°C to obtain a white gel. Take a mixture of 1.5 g potassium chloride and 1.5 g sodium chloride, grind them and pass them through a 100-mesh sieve, and add it to the white gel all at once. Keep stirring at 70°C for 15 minutes to obtain product C.

[0067] S3: After freeze-drying product C at -90℃ for 20 hours, place it in a tubular carbonization furnace, introduce nitrogen gas, heat from room temperature to 240℃ at a heating rate of 3℃ / min, hold at 240℃ for 1 hour, then heat to 1550℃ at a rate of 5℃ / min, hold at 1550℃ for 2 hours, and finally cool to room temperature at a rate of 4℃ / min to obtain a black solid product; wash the black solid product with 1M hydrochloric acid aqueous solution and then wash with water until neutral to obtain the product carbon material.

[0068] Example 9

[0069] S1: 10 g of chitosan hydrochloride and 4 g of polyvinylpyrrolidone were dissolved in 30 mL of deionized water and stirred at 70 °C for 40 minutes to obtain mixture A; 3 g of melamine phosphate and 3 g of cyanuric acid were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0070] S2: Divide the solid mixture B into 5 equal parts, and add 1 part to solution A every 10 minutes. Continue stirring at 70°C to obtain a white gel. Take 4 grams of potassium chloride, grind it and pass it through a 100-mesh sieve, and add it to the white gel all at once. Keep stirring at 70°C for 15 minutes to obtain product C.

[0071] S3: After freeze-drying product C at -90℃ for 20 hours, place it in a tubular carbonization furnace, introduce nitrogen gas, heat from room temperature to 240℃ at a heating rate of 3℃ / min, hold at 240℃ for 1 hour, then heat to 1550℃ at a rate of 5℃ / min, hold at 1550℃ for 2 hours, and finally cool to room temperature at a rate of 4℃ / min to obtain a black solid product; wash the black solid product with 1M hydrochloric acid aqueous solution and then wash with water until neutral to obtain the product carbon material.

[0072] Example 10

[0073] S1: 10 g of chitosan hydrochloride and 4 g of polyvinylpyrrolidone were dissolved in 200 ml of deionized water and stirred at 70 °C for 40 minutes to obtain mixture A; 3 g of melamine phosphate and 3 g of cyanuric acid were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0074] S2: Divide the solid mixture B into 10 equal parts, and add one part to solution A every 5 minutes. Continue stirring at 70°C to obtain a white gel. Take 4 grams of sodium chloride and grind it through a 100-mesh sieve. Add it to the white gel all at once and stir at 70°C for 15 minutes to obtain product C.

[0075] S3: After freeze-drying product C at -90℃ for 20 hours, place it in a tubular carbonization furnace, introduce nitrogen gas, heat from room temperature to 240℃ at a heating rate of 3℃ / min, hold at 240℃ for 1 hour, then heat to 1550℃ at a rate of 5℃ / min, hold at 1550℃ for 2 hours, and finally cool to room temperature at a rate of 4℃ / min to obtain a black solid product; wash the black solid product with 1M hydrochloric acid aqueous solution and then wash with water until neutral to obtain the product carbon material.

[0076] Comparative Example 1

[0077] S1: 10 g chitosan and 4 g polyvinylpyrrolidone were placed in 50 ml of deionized water and stirred at 70 °C for 40 minutes to obtain mixture A; 3 g melamine phosphate and 3 g cyanuric acid were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0078] S2: Divide the solid mixture B into 10 equal parts, and add one part to solution A every 5 minutes, while stirring continuously at 70°C; take 2 grams of potassium chloride and 2 grams of sodium chloride, grind them and pass them through a 100-mesh sieve, and add them all at once to the mixture of A and B, stirring at 70°C for 15 minutes to obtain product C.

[0079] S3: After freeze-drying product C at -90℃ for 20 hours, place it in a tubular carbonization furnace, introduce nitrogen gas, heat from room temperature to 240℃ at a heating rate of 3℃ / min, hold at 240℃ for 1 hour, then heat to 1550℃ at a rate of 5℃ / min, hold at 1550℃ for 2 hours, and finally cool to room temperature at a rate of 4℃ / min to obtain a black solid product; wash the black solid product with 1M hydrochloric acid aqueous solution and then wash with water until neutral to obtain the product carbon material.

[0080] Comparative Example 2

[0081] S1: 10 g of chitosan hydrochloride and 4 g of polyvinylpyrrolidone were dissolved in 50 mL of deionized water and stirred at 70 °C for 40 minutes to obtain mixture A; 3 g of urea phosphate and 3 g of cyanuric acid were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0082] S2: Divide the solid mixture B into 10 equal parts, and add one part to solution A every 5 minutes, while stirring continuously at 70°C; take 2 grams of potassium chloride and 2 grams of sodium chloride, grind them and pass them through a 100-mesh sieve, and add them all at once to the mixture of A and B, stirring at 70°C for 15 minutes to obtain product C.

[0083] S3: After freeze-drying product C at -90℃ for 20 hours, place it in a tubular carbonization furnace, introduce nitrogen gas, heat from room temperature to 240℃ at a heating rate of 3℃ / min, hold at 240℃ for 1 hour, then heat to 1550℃ at a rate of 5℃ / min, hold at 1550℃ for 2 hours, and finally cool to room temperature at a rate of 4℃ / min to obtain a black solid product; wash the black solid product with 1M hydrochloric acid aqueous solution and then wash with water until neutral to obtain the product carbon material.

[0084] Comparative Example 3

[0085] S1: 10 g of glucosamine hydrochloride and 4 g of polyvinylpyrrolidone were dissolved in 50 mL of deionized water and stirred at 70 °C for 40 minutes to obtain mixture A; 3 g of melamine phosphate and 3 g of cyanuric acid were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0086] S2: Divide the solid mixture B into 10 equal parts, and add one part to solution A every 5 minutes, while stirring continuously at 70°C; take 2 grams of potassium chloride and 2 grams of sodium chloride, grind them and pass them through a 100-mesh sieve, and add them all at once to the mixture of A and B, stirring at 70°C for 15 minutes to obtain product C.

[0087] S3: After freeze-drying product C at -90℃ for 20 hours, place it in a tubular carbonization furnace, introduce nitrogen gas, heat from room temperature to 240℃ at a heating rate of 3℃ / min, hold at 240℃ for 1 hour, then heat to 1550℃ at a rate of 5℃ / min, hold at 1550℃ for 2 hours, and finally cool to room temperature at a rate of 4℃ / min to obtain a black solid product; wash the black solid product with 1M hydrochloric acid aqueous solution and then wash with water until neutral to obtain the product carbon material.

[0088] Comparative Example 4

[0089] S1: 10 g of chitosan hydrochloride and 1.5 g of polyvinylpyrrolidone were dissolved in 50 mL of deionized water and stirred at 70 °C for 40 minutes to obtain mixture A; 3 g of melamine phosphate and 3 g of cyanuric acid were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0090] S2: Divide the solid mixture B into 10 equal parts, and add one part to solution A every 5 minutes, while stirring continuously at 70°C; take 2 grams of potassium chloride and 2 grams of sodium chloride, grind them and pass them through a 100-mesh sieve, and add them all at once to the mixture of A and B, stirring at 70°C for 15 minutes to obtain product C.

[0091] S3: After freeze-drying product C at -90℃ for 20 hours, place it in a tubular carbonization furnace, introduce nitrogen gas, heat from room temperature to 240℃ at a heating rate of 3℃ / min, hold at 240℃ for 1 hour, then heat to 1550℃ at a rate of 5℃ / min, hold at 1550℃ for 2 hours, and finally cool to room temperature at a rate of 4℃ / min to obtain a black solid product; wash the black solid product with 1M hydrochloric acid aqueous solution and then wash with water until neutral to obtain the product carbon material.

[0092] Comparative Example 5

[0093] S1: 10 g of chitosan hydrochloride and 4 g of polyvinylpyrrolidone were dissolved in 50 mL of deionized water and stirred at 70 °C for 40 minutes to obtain mixture A; 3 g of melamine phosphate and 3 g of cyanuric acid were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0094] S2: Divide the solid mixture B into 10 equal parts, and add one part to solution A every 5 minutes, while stirring continuously at 70°C; take 2 grams of potassium chloride and 2 grams of sodium chloride, grind them and pass them through a 100-mesh sieve, and add them all at once to the mixture of A and B, stirring at 70°C for 15 minutes to obtain product C.

[0095] S3: Dry product C at 50℃ and -0.09 MPa for 20 hours, place it in a tubular carbonization furnace, introduce nitrogen gas, heat from room temperature to 240℃ at a heating rate of 3℃ / min, hold at 240℃ for 1 hour, then heat to 1550℃ at a rate of 5℃ / min, hold at 1550℃ for 2 hours, and finally cool to room temperature at a rate of 4℃ / min to obtain a black solid product; wash the black solid product with 1M hydrochloric acid aqueous solution and then wash with water until neutral to obtain the carbon material.

[0096] Comparative Example 6

[0097] S1: 10 g of chitosan hydrochloride and 4 g of polyvinylpyrrolidone were dissolved in 50 mL of deionized water and stirred at 70 °C for 40 minutes to obtain mixture A; 3 g of melamine phosphate and 3 g of cyanuric acid were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0098] S2: Add solid mixture B to solution A and stir continuously at 70°C; take 2g of potassium chloride and 2g of sodium chloride, grind them and pass them through a 100-mesh sieve, add them all at once to the mixture of A and B, and stir at 70°C for 15 minutes to obtain product C.

[0099] S3: After freeze-drying product C at -90℃ for 20 hours, place it in a tubular carbonization furnace, introduce nitrogen gas, heat from room temperature to 240℃ at a heating rate of 3℃ / min, hold at 240℃ for 1 hour, then heat to 1550℃ at a rate of 5℃ / min, hold at 1550℃ for 2 hours, and finally cool to room temperature at a rate of 4℃ / min to obtain a black solid product; wash the black solid product with 1M hydrochloric acid aqueous solution and then wash with water until neutral to obtain the product carbon material.

[0100] Comparative Example 7

[0101] S1: 10 g of chitosan hydrochloride and 4 g of polyvinylpyrrolidone were dissolved in 50 mL of deionized water and stirred at 70 °C for 40 minutes to obtain mixture A; 3 g of melamine phosphate and 3 g of cyanuric acid were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0102] S2: Divide the solid mixture B into 10 equal parts, and add one part to solution A every 5 minutes, while stirring continuously at 70°C; take 2 grams of potassium chloride and 2 grams of sodium chloride, grind them and pass them through a 100-mesh sieve, and add them all at once to the mixture of A and B, stirring at 70°C for 15 minutes to obtain product C.

[0103] S3: After freeze-drying product C at -90℃ for 20 hours, place it in a tubular carbonization furnace, introduce nitrogen gas, raise the temperature from room temperature to 1550℃ at a rate of 5℃ / min, hold at 1550℃ for 2 hours, and finally lower it to room temperature at a rate of 4℃ / min to obtain a black solid product; wash the black solid product with 1M hydrochloric acid aqueous solution and then wash with water until neutral to obtain the product carbon material.

[0104] Comparative Example 8

[0105] S1: 10 g of chitosan hydrochloride and 4 g of polyethylene glycol were dissolved in 50 mL of deionized water and stirred at 70 °C for 40 minutes to obtain mixture A; 3 g of melamine phosphate and 3 g of cyanuric acid were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0106] S2: Divide the solid mixture B into 10 equal parts, and add one part to solution A every 5 minutes, while stirring continuously at 70°C; take 2 grams of potassium chloride and 2 grams of sodium chloride, grind them and pass them through a 100-mesh sieve, and add them all at once to the mixture of A and B, stirring at 70°C for 15 minutes to obtain product C.

[0107] S3: After freeze-drying product C at -90℃ for 20 hours, place it in a tubular carbonization furnace, introduce nitrogen gas, heat from room temperature to 240℃ at a heating rate of 3℃ / min, hold at 240℃ for 1 hour, then heat to 1550℃ at a rate of 5℃ / min, hold at 1550℃ for 2 hours, and finally cool to room temperature at a rate of 4℃ / min to obtain a black solid product; wash the black solid product with 1M hydrochloric acid aqueous solution and then wash with water until neutral to obtain the product carbon material.

[0108] Comparative Example 9

[0109] S1: 7 g of chitosan hydrochloride and 7 g of polyvinylpyrrolidone were dissolved in 50 mL of deionized water and stirred at 70 °C for 40 minutes to obtain mixture A; 3 g of melamine phosphate and 3 g of cyanuric acid were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0110] S2: Divide the solid mixture B into 10 equal parts, and add one part to solution A every 5 minutes, while stirring continuously at 70°C; take 2 grams of potassium chloride and 2 grams of sodium chloride, grind them and pass them through a 100-mesh sieve, and add them all at once to the mixture of A and B, stirring at 70°C for 15 minutes to obtain product C.

[0111] S3: After freeze-drying product C at -90℃ for 20 hours, place it in a tubular carbonization furnace, introduce nitrogen gas, heat from room temperature to 240℃ at a heating rate of 3℃ / min, hold at 240℃ for 1 hour, then heat to 1550℃ at a rate of 5℃ / min, hold at 1550℃ for 2 hours, and finally cool to room temperature at a rate of 4℃ / min to obtain a black solid product; wash the black solid product with 1M hydrochloric acid aqueous solution and then wash with water until neutral to obtain the product carbon material.

[0112] Comparative Example 10

[0113] S1: 10 g of chitosan hydrochloride and 4 g of polyvinylpyrrolidone are ground through a 100-mesh sieve to obtain mixture A; 3 g of melamine phosphate and 3 g of cyanuric acid are mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0114] S2: Divide solid mixture B into 10 equal parts, and add one part to A every 5 minutes while stirring continuously; take 2 grams of potassium chloride and 2 grams of sodium chloride, grind them and pass them through a 100-mesh sieve, and add them all at once to the mixture of A and B, keep at 70°C and stir for 15 minutes to obtain product C.

[0115] S3: Product C was placed in a tubular carbonization furnace, nitrogen gas was introduced, and the temperature was increased from room temperature to 240℃ at a rate of 3℃ / min. After holding at 240℃ for 1 hour, the temperature was increased to 1550℃ at a rate of 5℃ / min and held at 1550℃ for 2 hours. Finally, the temperature was decreased to room temperature at a rate of 4℃ / min to obtain a black solid product. The black solid product was washed with 1M hydrochloric acid aqueous solution and then washed with water until neutral to obtain the carbon material. The content of N and P in the product was analyzed by X-ray photoelectron spectroscopy. The results showed that the N content was 3.15% and the phosphorus content was 0.15%.

[0116] Comparative Example 11

[0117] S1: 10 g of chitosan hydrochloride and 4 g of polyvinylpyrrolidone were placed in 50 mL of deionized water and stirred at room temperature for 40 minutes to obtain mixture A; 3 g of melamine phosphate and 3 g of cyanuric acid were mixed and ground through a 100-mesh sieve to obtain solid mixture B;

[0118] S2: Divide the solid mixture B into 10 equal parts, and add one part to solution A every 5 minutes while stirring continuously; take 2 grams of potassium chloride and 2 grams of sodium chloride, grind them and pass them through a 100-mesh sieve, add them all at once to the mixture of A and B, stir for 15 minutes to obtain product C.

[0119] S3: After freeze-drying product C at -90℃ for 20 hours, it was placed in a tubular carbonization furnace, nitrogen gas was introduced, and the temperature was increased from room temperature to 240℃ at a rate of 3℃ / min. After holding at 240℃ for 1 hour, the temperature was increased to 1550℃ at a rate of 5℃ / min and held at 1550℃ for 2 hours. Finally, the temperature was decreased to room temperature at a rate of 4℃ / min to obtain a black solid product. The black solid product was washed with 1M hydrochloric acid aqueous solution and then washed with water until neutral to obtain the carbon material. The content of N and P in the product was analyzed by X-ray photoelectron spectroscopy. The results showed that the N content was 3.06% and the phosphorus content was 0.12%.

[0120] Test Example 1: Nitrogen Adsorption-Desorption Test

[0121] The nitrogen adsorption-desorption tests were performed on the carbon materials doped with nitrogen and phosphorus heteroatoms obtained in Examples 1-8 and Comparative Examples 1-11, and the results are shown in Table 1.

[0122] Table 1. Properties of the nitrogen- and phosphorus-doped carbon materials obtained in Examples 1-8 and Comparative Examples 1-11

[0123]

[0124] Test Example 2

[0125] 100 parts of natural rubber, 30 parts of reinforcing agent (selected from one of the carbon materials obtained in Examples 1-8 and Comparative Examples 1-11), 6 parts of activator (zinc oxide), 1 part of stearic acid, 17 parts of softener (petroleum resin), 3 parts of antioxidant (MB), 2 parts of accelerator (CZ), 25 parts of filler (FD170), and 4.5 parts of vulcanizing agent (sulfur).

[0126] S1: Plasticizing

[0127] Set the initial temperature of the internal mixer to 70℃ and the speed to 40 rpm. Cut the natural rubber into small pieces and add them to the internal mixer. Plasticize for 6 minutes, and discharge when the temperature of the mixing chamber reaches 100℃. Pass the mixture through a thin mill on an open mill, form triangular bundles 4 times, and let it stand for at least 8 hours before use.

[0128] S2: A Mixture

[0129] Set the initial temperature of the internal mixer to 85℃ and the rotation speed to 35 rpm. Add the masticated natural rubber to the internal mixer. After approximately 45 seconds, lift the top plug and add the reinforcing agent, filler, activator, stearic acid, softener, and antioxidant. Press down the top plug and mix for 160 seconds, raising the plug once midway. Discharge the rubber at 110℃. After a section of the mixed rubber falls into the open mill, adjust the roll gap to 5mm and automatically pour the rubber 4 times, ensuring the open mill roll temperature does not exceed 60℃. After pouring, sheet the rubber and let it rest for at least 8 hours before use.

[0130] S3: Two-stage mixing

[0131] Set the initial temperature of the internal mixer to 85℃ and the rotation speed to 35 rpm. Feed the first stage of the compound into the internal mixer, pressurize for 45 seconds, then lift the top bolt to add the vulcanizing agent and accelerator. Press down the top bolt and mix for 80 seconds at a mixing temperature of 110℃, then discharge the compound. After the second stage of the compound falls into the open mill, adjust the roller gap to 5mm, and automatically pour the compound four times, ensuring the open mill roller temperature does not exceed 60℃. After pouring, sheet the compound and allow it to stand for at least 8 hours before use to obtain the corresponding sample.

[0132] The sample obtained by using the carbon material in a certain embodiment or comparative example as the reinforcing agent is recorded as the sample corresponding to the corresponding embodiment or comparative example.

[0133] According to Q / CR 562.2-2017 "Railway Tunnel Drainage and Waterproofing Materials Part 2: Waterstops", the performance of the corresponding samples was tested, and the results are shown in Table 2.

[0134] Table 2

[0135]

[0136]

[0137] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A carbon material doped with nitrogen and phosphorus heteroatoms, characterized in that, The preparation method is as follows: S1: Dissolve the carbon source and polyvinylpyrrolidone in water and stir to obtain mixture A; mix and grind melamine phosphate and nitrogen source to obtain solid mixture B; S2: Under heating and stirring, solid mixture B is added to mixture A in portions to obtain a gel; under continuous heating and stirring, chloride salt is added to the gel and stirred evenly to obtain intermediate product C; S3: After freeze-drying the intermediate product C, it is placed in a tube furnace and calcined in a protective atmosphere to obtain a black solid. After post-processing, carbon material is obtained. The calcination is as follows: the temperature is increased from room temperature to 180-300℃ at a rate of 2-4℃ / min and held for 0.5-1.5h; the temperature is increased to 1450-1650℃ at a rate of 4-6℃ / min and held for 1-3h; and finally the temperature is reduced to room temperature at a rate of 3-5℃ / min. The carbon source includes one or more of chitosan hydrochloride, chitobiose hydrochloride, and chitotetraose tetrahydrochloride; The nitrogen source includes one or more of cyanuric acid, thiocyanuric acid, cyanuric acid diamide, and hexachlorotriphosphazene. The chloride salt is sodium chloride and / or potassium chloride; The mass ratio of the carbon source, melamine phosphate, nitrogen source, polyvinylpyrrolidone, and chloride salt is 10:2~4:2~4:3~5:3~5.

2. The carbon material doped with nitrogen and phosphorus heteroatoms according to claim 1, characterized in that, In S1, the ratio of carbon source to water is 1g: 3~20ml.

3. The carbon material doped with nitrogen and phosphorus heteroatoms according to claim 1, characterized in that, The mass ratio of the carbon source, melamine phosphate, nitrogen source, polyvinylpyrrolidone, and chloride salt is 10:3:3:4:

4.

4. The carbon material doped with nitrogen and phosphorus heteroatoms according to claim 1, characterized in that, The stirring temperature in S1 is 50~90℃, and the stirring time is 30~50min; The heating and stirring temperature in S2 is 50~90℃.

5. A carbon material doped with nitrogen and phosphorus heteroatoms according to claim 1, characterized in that, The freeze-drying temperature is -80 to -100°C; the freeze-drying time is 15 to 25 hours.

6. The carbon material doped with nitrogen and phosphorus heteroatoms according to claim 1, characterized in that, The post-treatment involves washing with 0.1-2M hydrochloric acid followed by rinsing with water until no chlorine residue remains.

7. A method for preparing a carbon material doped with nitrogen and phosphorus heteroatoms as described in any one of claims 1 to 6.

8. The application of a carbon material doped with nitrogen and phosphorus heteroatoms as described in any one of claims 1 to 6 in the field of rubber waterstops.

Citation Information

Patent Citations

  • Preparation method and application of nitrogen-containing porous carbon material based on polyaspartic acid salt

    CN110577206A

  • Nitrogen-phosphorus doped porous carbon material as well as preparation method and application thereof

    CN110615424A

  • Preparation method of nitrogen, phosphorus and iron doped carbon material and application of nitrogen, phosphorus and iron doped carbon material in rubber

    CN116986584A